ANALYSIS OF PSYCHOMOTOR STRUCTURES TONICITY AND BALANCE OF FEMALE ELDERES THAT PRACTICE TAI CHI CHUAN (Fiep Bulletin - online, 2015)
This study aimed to investigate the tonicity and balance levels of female elders in a Tai Chi Chuan training program, over a time span of six months between pre and post testing.Our research group selected nineteen female elders, ranging from sixty to sixty three years old, and who practiced Tai Chi Chuan  three times a week for an hour. In order to gather the data, we applied two subtests of Bateria Psicomotora (BPM) - developed by Fonseca (1995)  refering to tonicity and balance.  In addition, the comparative results of the  hypothesis tests (Student t-test) had a level of significance p < 0.05, followed by a comparative analysis of the average of the two time span limits (pre and post testing), reaching a qualitative diagnosis, with average values related to “Worsening”, “Same” and “”Improvement”. From the thirty two analysed aspects: nineteen showed some improvement,  thirteen remained the same and there was no evidence of worsening.  Over all, 59% of their motor skills improved and 41% were equal.  The data demonstrated that during our time range of six months, there was a significant improvement of the psycomotor aspects of tonicity and balance.   The elders responded positively to the study´s hyphotesis:  Tai Chi Chuan as an efficient contributor to psychomotor bettering in relation to tonicity and balance.
Keywords: Tai Chi Chuan; elders; tonicity and equilibration